Student Digipreneur: The Role of Peer Team-Based Learning and Project-Based Learning - Jarot Tri Bowo Santoso; Ahmad Nurkhin (Fakultas Ekonomi, Universitas Negeri Semarang, 2022)
This study aimed to analyze the role of peer team-based learning (PTBL) and project-based learning (PJBL) in increasing student digitpreneurs. This Action Research was conducted in 2 cycles, namely, cycle 1 using Peer Team-Based Learning and cycle 2 using Project-Based Learning. The population in this study were 123 students of Accounting Economics Education, Class of 2018 at the Faculty of Economics, UNNES who took digital business courses and used a saturated sample. Data was collected through tests, questionnaires, and documentation. Questionnaire data were analyzed with quantitative descriptive analysis. The results showed that (1) the application of PTBL in digital business learning played a role in increasing the number of student digipreneurs in Accounting Education FE UNNES, a total of 32 people (26.02%) or 7 groups, (2) the application of PJBL in digital business learning played a role in increasing the number of student digipreneurs, totally (69.10%) or 20 groups, (3) the implementation of PJBL was more effective in increasing the number of student digipreneurs by 85 people (69.10%) compared to PTBL. Future research is suggested to apply learning methods that are more varied in subjects related to sustainable entrepreneurship and sustainable entrepreneurship assessment.